An Approach to Determine Noise Model Parameter for Submicron MOSFET from RF Noise Figure Measurement - Hanqi Gao; Jing Jin; Jianjun Zhou (IEEE Journal of the Electron Devices Society, 2024)
An extraction method to obtain the noise model parameter $T_{ d}$ in deep submicron MOSFETs directly from radio frequency (RF) scattering parameters and noise figure measurements is presented. A simplified noise equivalent circuit, along with closed-form solutions to calculate the RF noise figure of MOSFET is developed. On-wafer experimental verification is presented and a comparison with tuner based method is given. Good agreement is obtained between simulated and measured results for $16× 1× 2{{μ }\rm m}$ (number of gate fingers $× $ unit gatewidth $× $ cells) gatelength MOSFETs.